History of childhood abuse is associated with less positive treatment outcomes in socially stable women with alcohol use disorder - Fides Schückher; Tabita Sellin; Ingemar Engström; Kristina Berglund (BMC, 2019)
Abstract Background To examine the relationship between treatment outcome, as measured according to change in alcohol consumption, and a history of childhood abuse (emotional, physical, sexual) in socially stable women undergoing treatment for alcohol use disorder (AUD). Methods Participants were assessed using the Addiction Severity Index and the Mini International Neuropsychiatric Interview at the beginning of treatment (n = 75), end of treatment (n = 59) and 12 month follow-up after treatment (n = 57). Self-report data on alcohol consumption were obtained at all three time-points using the Alcohol Habits Inventory-Revised 2. Self-report data on childhood maltreatment were obtained at the beginning of treatment using the Childhood Trauma Questionnaire-short form. Study outcomes were changes in alcohol consumption (grams of pure alcohol per week), risk-drinking and reported abstinence. Results Of the 75 women enrolled, 38 (50.7%) reported a history of childhood abuse and the rest did not. Both groups showed a significant improvement in all three outcomes at the end of treatment and at 12-month follow-up. At the end of treatment, a significant inter-group difference was found for reported abstinence (non-abused group, 39.3% vs abused, 12.9%; p < 0.05). At 12-month follow-up, significant inter-group differences were observed for all treatment outcomes, with superior outcomes being found for the non-abused group, including a higher proportion of women with reported abstinence (55.6% vs 13.3%; p < 0.01). Conclusion The present findings suggest that an evaluation of a possible history of childhood abuse is warranted in all women seeking treatment for AUD, irrespective of social stability. In terms of clinical practice, the results suggest that additional interventions may be warranted in this population.